2019
DOI: 10.18410/jebmh/2019/572
|View full text |Cite
|
Sign up to set email alerts
|

Lp(a), ApoB and ApoB/ApoA1 Ratio as Potential Serum Markers for Predicting Early-Onset Acute Coronary Syndrome

Abstract: BACKGROUND Prevalence of coronary artery disease is higher in elderly population (>60 years) however, it is increasingly seen in younger population due to change in lifestyle. Lipoprotein a [Lp(a)], Apolipoprotein B (ApoB) and Apolipoprotein A1 are among the emerging markers for acute coronary syndrome (ACS). Routine lipid profile does not incorporate these markers and cardiovascular diseases (CVD) in young individuals who show marked derangement in their blood biochemical profile. In this study we assessed Lp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…In the study carried out by Hong et al on 280 patients with NSTEMI who underwent PCI; Apo B and Apo B/Apo A1 ratios were associated with the total occlusion of infarction-related artery in the cases [ 20 ]. More recently, Rebecca et al conducted research on 75 cases with ACS and 69 controls, and they suggested that adding ApoB and ApoB/ApoA1 to the traditional lipid profile would be more helpful in predicting early onset ACS [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study carried out by Hong et al on 280 patients with NSTEMI who underwent PCI; Apo B and Apo B/Apo A1 ratios were associated with the total occlusion of infarction-related artery in the cases [ 20 ]. More recently, Rebecca et al conducted research on 75 cases with ACS and 69 controls, and they suggested that adding ApoB and ApoB/ApoA1 to the traditional lipid profile would be more helpful in predicting early onset ACS [ 21 ].…”
Section: Discussionmentioning
confidence: 99%